الحقوق الأساسية لذوي الإعاقة في الشريعة الإسلامية = The basic rights of disability in Sharia - Ahmad Muhamad Abdulah Al-Ali, Fatemah; Arif, Arif Ali (Program Studi Hukum Keluarga (Akhwal Syakhsiah), Fakultas Ilmu Agama Islam, Universitas Islam Indonesia, 2019)
يسلط هذا البحث الضوء على الحقوق الأساسية والصحية للمعوق؛ لما في ذلك من أهمية كبرى تتعلق بحياة الإنسان وصحته، وترتبط ارتباطاً وثيقاً بمدى فاعليته في المجتمع، وقدرته على المشاركة فيه، خاصة مع الجهل المتفشي في بعض شرائح المجتمع عن حقوق الشخص المعوّق، أو الاستهانة بها وبشخصيته وكيانه، وإهدار كرامته بالاستهزاء به، واستغلال ضعفه وقلة حيلته، فمحاور البحث تدور حول حقوق المعوّق الأساسية بالإضافة إلى بيان الجانب الوقائي للحد من الإعاقة وتجنبها، فجاء البحث ليوضح أولاً الحقوق الأساسية عموماً وما تحتويه من فروع، كحق الحياة، والكرامة، والمساواة والعدالة والتعليم والعمل والخصوصية، وثانياً الحقوق الصحية بوجه خاص، من جانب الوقاية، ورعاية الشريعة الإسلامية الطبية العلاجية، ويعتمد البحث المنهج الاستقرائي والتحليلي في تتبع شواهد اهتمامات الشريعة الإسلامية في المراجع الفقهية، وأهم ما جاء في نتائج هذا البحث أن الإسلام حفظ للمعوّق إنسانيته وكرامته وحرّم التعدي عليها؛ ليعيش بالشكل الذي يجعله مندمجاً مع غيره في مجتمعه دون الشعور بالذل أو الإهانة، وأن الشريعة الإسلامية أرشدتنا للوقاية من الأمراض والإعاقات، والمحافظة على النفس والبدن. وأما محاور البحث فتتضمن أربعة مباحث. *************************************************************************************** This research highlights the basic rights of disabled, owing to the great importance of these rights to human life and his health, and the close relationship of those rights with the effectiveness of disabled and his ability to function and participate in society. Especially, with the widespread ignorance in some sectors about the rights of the disabled, or derogating him, his personality, and wasting his dignity by mocking him and exploiting his weakness and silliness. The study in this research revolves around the basic rights of disabled as well as the preventive aspect to reduce and avoid disability. So, the research firstly clarifies the basic rights and their contents, such as the right to life, dignity, equality, justice, education, work and privacy. Secondly, it discusses the health rights from the aspect of prevention and the care of Islam about the therapeutic medicine. The inductive and analytical methods are used in the research to search for the evidence in the jurisprudential references on the concern of Islam about the therapeutic medicine.